The European Union facing climate change: a window of opportunity for technological development and entrepreneurship - Ana Zuazua Ruiz; José María Martín Martín; Juan F Prados-Castillo (Sustainable Technology and Entrepreneurship, 2023)
The fight against climate change is one of the significant challenges of the 21st century. The European Union's environmental policy has evolved as the perception of the problem has become more evident. This paper examines the environmental commitments made by the European Union on the global scene to verify its involvement and responsibility in environmental policy. A comprehensive analysis of the European Union's environmental policies compared to other countries has been carried out using a comparative methodological framework of these commitments. The results confirm the European Union's leadership in promoting and implementing policies to combat climate change and environmental sustainability, which therefore opens windows of opportunity for technological development and entrepreneurship. Future lines of research are proposed following the conclusions, considering the current economic and environmental situation in an environment of energy crisis and inflation.